Income, Subjective Norms, Policy Uncertainty, and Saving Behavior: The Mediating Role of Saving Intention: JEL Classification: D14, D91, E21, G41, H31 - Bayu Priyana; Achmad Kautsar (Journal La Bisecoman, 2026)
Product (GRDP) in East Java, the real sector actually experienced a contraction, which forces the society to be more active in saving. The objective of this study is to analyze the effect of subjective norms, income, and policy uncertainty on the saving behavior of workers in Kediri City, as well as to examine the role of saving intention as a mediating variable. This study employs a quantitative approach using a survey method with a 5-point Likert scale questionnaire. The sample consisted of 100 productive-age workers selected through a proportional cluster sampling technique across three administrative areas. Data were analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) approach via SmartPLS software version 4.1.1.7. The results indicate that subjective norms have a positive and significant effect on both saving intention and saving behavior directly. Policy uncertainty and saving intention are also proven to have a significant positive effect on saving behavior. However, the income level is found to have no significant effect on workers' saving behavior. In conclusion, encouragement from the immediate social environment and concerns over future regulatory conditions are crucial factors shaping precautionary saving behavior, whereas the amount of income is not the main determinant without a strong intention.